De não-professor a professor: uma reflexão sobre a construção da identidade profissional de professores de cursos superiores de formação tecnológica - Toledo, Rodrigo (2011)
The objective of this research is to analyze the building process of technology college teacher’s professional identity. One coined the expression “non-teacher” to design the professionals that are challenged to build a teaching professional identity to which, in thesis, didn’t receive specific training. For different reasons, 7 participants that lecture in Private Colleges Institutions at São Paulo city were selected. As gathering information procedure it was applied letter writing with a set of recommendation to a newcomer teacher, whose analyses discourse tried to be based upon quality research methodology. The data analyses was guided by authors like Castells (1999); Dejours (1999); Dubar (2009); Furlanetto (2003); Tardif and Lessard (2009), among others. The results indicate that a strong identification figure to the participants is the director or supervisor, such as managers of business organizations, which allows attribution and belonging in the teaching exercise. In front of this discovery, it is possible to confirm that we are looking at the beginning of a new teaching way that needs more attention from education policies and the College Institutions that offers technologic degree